(untitled) (Bangladesh Journal of Botany, 2011)
Three East Anatolia species of Allium namely, A. karsianum Fomin, A. kunthianum Vved., A. rupestre Steven are compared morphologically and anatomically. The results showed that all the species investigated can be distinguished by their morphological and anatomical characters. Key words: Allium; Anatomy; Morphology DOI: http://dx.doi.org/10.3329/bjb.v40i1.7990 Bangladesh J. Bot. 40(1): 9-15, 2011 (June)